2021
DOI: 10.1039/d1fo01260f
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-432 inhibits milk fat synthesis by targeting SCD and LPL in ovine mammary epithelial cells

Abstract: In our previous studies, microRNA-432 (miR-432) was found to be one of differentially expressed miRNAs in ovine mammary gland between the two breeds of lactating sheep with different milk production...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The effect of oar-miR-432 of ovine preadipocytes on the induced differentiation has not been reported previously. It has been shown that miR-432 inhibited milk fat synthesis in sheep mammary epithelial cells ( Hao et al, 2021 ). During myoblast proliferation and differentiation, miR-432 was negatively regulated in pigs ( Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of oar-miR-432 of ovine preadipocytes on the induced differentiation has not been reported previously. It has been shown that miR-432 inhibited milk fat synthesis in sheep mammary epithelial cells ( Hao et al, 2021 ). During myoblast proliferation and differentiation, miR-432 was negatively regulated in pigs ( Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, miRNA-seq and mRNA-seq were used to identify potential miRNAs and mRNA related to sheep fat deposition in Hu fat-tailed and Tibetan thin-tailed sheep breeds. The oar-miR-432 associated with fat synthesis was identified, which is also one of the most downregulated miRNAs ( Hao et al, 2021 ). The TargetScan, miRanda, and RNAhybrid packages of software were used to predict the potential target genes of oar-miR-432 ( John et al, 2004 ; Krüger and Rehmsmeier, 2006 ; Agarwal et al, 2015 ) and putative target genes that overlapped with differentially expressed genes (DEGs).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, VLDLR also strengthens the activity of LPL that releases long-chain fatty acids from chylomicron and very low-density lipoprotein. Longchain fatty acids are used as raw materials for synthesizing triglycerides in MECs (13). In addition, knockout mice of VLDLR exhibited a decrease in adipocyte triglyceride storage (30).…”
Section: Discussionmentioning
confidence: 99%
“…The OMECs were isolated according to the method of Hao et al (13). Briefly, cells were cultured in a basal DMEM/F12 medium (Invitrogen, CA, USA) consisting of 10% fetal bovine serum, 5 µg/ml hydrocortisone, 5 µl/ml insulin-transferrinsodium selenium, 10 ng/ml epidermal growth factor 1, and 1 µg/ml hydrocortisone.…”
Section: Animals and Cell Culturementioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small, evolutionarily conserved non-coding RNA molecules (~22 nucleotides). They can inhibit translation or promote the degradation of the target mRNAs at a post-transcriptional level by complementarily binding to the 3′-untranslated regions (3′-UTR) of the target genes [ 5 ]. Previous studies have suggested that miRNAs have important roles in regulating the development of SMSCs.…”
Section: Introductionmentioning
confidence: 99%